Cutaneous fungal infections in solid organ transplant recipients - Ana Gusmão Palmeiro; João Borges-da-Costa (Revista da Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Long-term exposure to immunosuppressive drugs is a significant risk factor for the development of both cancers and infections. Solid-organ transplant recipients benefit from dermatology follow-up, allowing early diagnosis and treatment of these conditions.